PENGARUH GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL PEMODERASI (Studi Pada Dinas Kesehatan Kabupaten Bulungan) - Kasman; Syahran; Urip Pratomo (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2021)
This study aims to see the effect of leadership style and job compensation on job satisfaction and employee performance. The research site was the Bulungan District Health Office. All employees are 60 people who are the respondents' research. The approach used is quantitative with a research instrument in the form of a Likert scale questionnaire. The analytical tool used is path analysis with SPSS-AMOS 20 software. The findings in this study indicate that leadership style has no significant negative effect on employee performance with an influence coefficient of -0.29 and P-value of 0.053. Leadership style has a significant positive effect on job satisfaction with an influence coefficient of 0.51 and P-value of ***. Work compensation has a significant positive effect on job satisfaction with an influence coefficient of 0.29 and P-value of 0.005. Work compensation has no significant positive effect on employee performance with an influence coefficient of 0.09 and P-value of 0.516. Job satisfaction has no significant positive effect on employee performance with an influence coefficient of 0.12 and P-value of 0.440. The influence of leadership style and work compensation variables on data variations on job satisfaction variables is 39%, the remaining 61%, other variables outside this study. The influence of leadership style variables, compensation and job satisfaction on data variations on employee performance variables is 9%, the remaining is 91%, other variables outside this study.